2020
DOI: 10.1159/000507760
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Multidisciplinary Management Plan Is Effective in Reducing the Prevalence of Overweight and Obesity in Childhood and Adolescence

Abstract: Background: Obesity in childhood and adolescence represents a major health problem of our century. In Greece, 30-35% of children and adolescents are overweight or obese. Objective and Hypotheses: To investigate the effectiveness of a comprehensive multidisciplinary personalized management plan at reducing the prevalence of overweight and obesity in childhood and adolescence. Patients and Methods: One thousand (n = 1,000) children and adolescents aged 2-18 years (mean age ± SD: 10.09 ± 2.86 years; 520 females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…It is characterized by the increased accumulation of body fat, especially visceral adipose tissue. BMI (body weight in kilograms divided by the square of height in meters) is used as the standard clinical measure of overweight and obesity, although it has limitations when it is applied for muscular subjects, given that it cannot distinguish between lean and fat mass and fat mass distribution [8,9]. According to WHO, for adults, overweight corresponds to a BMI between 25-30 kg/m 2 and obesity to a BMI > 30 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the increased accumulation of body fat, especially visceral adipose tissue. BMI (body weight in kilograms divided by the square of height in meters) is used as the standard clinical measure of overweight and obesity, although it has limitations when it is applied for muscular subjects, given that it cannot distinguish between lean and fat mass and fat mass distribution [8,9]. According to WHO, for adults, overweight corresponds to a BMI between 25-30 kg/m 2 and obesity to a BMI > 30 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the early implementation of multidisciplinary personalized intervention programs for the prevention and management of overweight and obesity in childhood and adolescence is imperative. Several lifestyle intervention strategies have been proposed, which mostly involve a healthy lifestyle of diet, sleep and physical activity [ 7 , 8 , 9 ]. In addition, novel e-health applications have been developed to address the epidemic of childhood obesity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, more than 3,000 children and adolescents are followed up on a regular basis. We demonstrated that this personalized multi-disciplinary management plan is effective in reducing the prevalence of obesity in childhood and adolescence after one year of intervention [15,16].…”
Section: A/the Hellenic National Registry For the Prevention And Manamentioning
confidence: 91%
“…On both occasions, the tape did not compress the skin and was parallel to the floor. Blood pressure was determined by a sphygmomanometer (Comfort 20/40, Visomat, Parapharm, Metamorphosi, Attiki, Greece) and with an appropriate cuff according to the age of the subject [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The progressively increasing prevalence of overweight and obesity in childhood and adolescence in Greece, and possibly other countries, indicates that our current health policies are not effective, and that further developments in health policy strategies are required. To address this problem in our country, we developed the ‘National e-Health Program for the Prevention and Management of Overweight and Obesity in Childhood and Adolescence’, which provides specific and detailed guidance to all primary health care physicians about the personalized management of overweight or obese children and adolescents [ 13 , 14 ]. The ‘National e-Health Program for the Prevention and Management of Overweight and Obesity in Childhood and Adolescence’ is a National Program available to all Pediatricians and General Practitioners in our country, who—through a web application—register online all children and adolescents nationwide, and receive guidance and detailed advice regarding their management depending on their BMI [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%